Electric Field Enhancement Effect of Aluminum Grating With Nanosecond Pulsed Laser Irradiation - Wang, Jiamin; Zhang, Kuo; Yu, Jinghua; Zhang, Yin; Ji, Yanhui; Jirigalantu,; Zhang, Wei; Li, Wenhao; Zheng, Changbin; Chen, Fei (Frontiers in Physics, 2022)
Aluminum grating is widely used in laser systems and photoelectric equipments. Research on the laser damage characteristics of aluminum grating is of guiding significance and application value for improving the laser damage resistance. To better understand the laser damage characteristics of aluminum grating, based on the finite-difference time-domain method, the Maxwell’s equations are solved numerically, and the electric field model of 1064nm Gaussian laser damage aluminum grating is established. The simulation results show that the light field is modulated by the grating, the maximum value of the electric field occurs at the ridge of the grating. Analysis suggests that and the electric field distribution is in accordance with the laser energy distribution. The distribution region of maximum electric field is the vulnerable location. To further verify the local electric-field enhancement effect, based on 1-on-1 laser damage measurement method, an experimental study of nanosecond laser (@1064 nm, 6.5 ns) damage to the aluminum grating was carried out, and the damage morphology was analysed through SEM, which found that the simulation results showed good agreement with the experimental results.